FAKTOR YANG MEPENGARUHI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) BADAN USAHA MILIK DESA - Muhammad Hengki Setiawan; Prayekti Prayekti; I. Soni Kurniawan (Universitas Muhammadiyah Yogyakarta, 2020)
The writer wants to know the factors that influence OCB in BUMDes Panggung Lestari Panggungharjo Village Sewon District Bantul Regency. The analytical method used is the classical assumption test, t test and sobel test. Based on the results of this study note that, individual characteristics and affective commitment have a significant positive effect on intrinsic motivation, intrinsic motivation has a significant positive effect on organizational citizenship behavior, individual characteristics have a significant positive effect on organizational citizenship behavior, affective commitment has no significant effect on organizational citizenship behavior and individual characteristics, affective commitment has a significant positive effect on organizational citizenship behavior with intrinsic motivation variables as intervening variables. It is hoped that this research can be used to measure individual character, commitment and motivation towards organizational citizenship behavior.